Monitoring acute metabolic changes in the liver and kidneys induced by fructose and glucose using hyperpolarized [2‐13C]dihydroxyacetone. Issue 1 (17th November 2016) - Marco‐Rius, Irene; von Morze, Cornelius; Sriram, Renuka; Cao, Peng; Chang, Gene‐Yuan; Milshteyn, Eugene; Bok, Robert A.; Ohliger, Michael A.; Pearce, David; Kurhanewicz, John; Larson, Peder E.Z.; Vigneron, Daniel B.; et al.
Abstract : Purpose: To investigate acute changes in glucose metabolism in liver and kidneys in vivo after a bolus injection of either fructose or glucose, using hyperpolarized [2‐ 13 C]dihydroxyacetone. Methods: Spatially registered, dynamic, multislice MR spectroscopy was acquired for the metabolic products of [2‐ 13 C]dihydroxyacetone in liver and kidneys. Metabolism was probed in 13 fasted rats at three time points: 0, 70, and 140 min. At 60 min, rats were injected intravenously with fructose (n = 5) or glucose (n = 4) at 0.8 g/kg to initiate acute response. Controls (n = 4) did not receive a carbohydrate challenge. Results: Ten minutes after fructose infusion, levels of [2‐ 13 C]phosphoenolpyruvate and [2‐ 13 C]glycerol‐3‐phosphate halved in liver: 51% ( P = 0.0010) and 47% ( P = 0.0001) of baseline, respectively. Seventy minutes later, levels returned to baseline. The glucose challenge did not alter the signals significantly, nor did repeated administration of the dihydroxyacetone imaging bolus. In kidneys, no statistically significant changes were detected after sugar infusion other than a 20% increase of the glycerol‐3‐phosphate signal between 10 and 80 min after fructose injection ( P = 0.0028). Conclusion: Hyperpolarized [2‐ 13 C]dihydroxyacetone detects a real‐time, transient metabolic response of the liver to an acute fructose challenge. Observed effects possibly include ATP depletion and changes in the unlabeled pool sizes of glycolytic intermediates. Magn Reson Med 77:65–73, 2017. © 2016 International Society for Magnetic Resonance in Medicine